Development of Interactive Multimedia Based on ISpring Suite with Corrective Feedback to Improve Student’s Conceptual Understanding Ability - Fajar Kurnia Awala; Yesi Franita; Zuida Ratih Hendrastuti (RANGE: Jurnal Pendidikan Matematika, 2024)
The ability to understand mathematical concepts are one of the abilities that must be achieved. Based on the results of the initial test, the conceptual understanding ability of class IX students at one of schools in Magelang are relatively low. The aim of this research was to produce iSpring Suite-based learning multimedia products with valid, practical and effective corrective feedback in improving students' concept understanding abilities. The research belongs to research and development using the Borg and Gall model. The results of the validity test were 88.44% by material experts in the "very valid" category, and 80.77% by multimedia experts in the "very valid" category. The results of the practicality test were based on the results of the student response questionnaire with an average score percentage of 90% in the "very practical" category, then based on the teacher response questionnaire with a percentage of 88% in the "very practical" category, and based on learning implementation questionnaire, the score was 93.33% with the "very good" category. The results of the test involving 32 students based on the N-Gain were 0.71 in the high improvement category, and the Wilcoxon test obtained Z = -4.941. So, interactive multimedia based on ISpring Suite with Corrective Feedback are valid, practical and effective to improve junior high school students' concept understanding skills in quadratic equation material.